The importance of the pharmacist in the adherence to Antiretroviral Therapy (ART) in the management of care in HIV/AIDS - Silva, Alessandro Tavares da (2022)
HIV emerged in the early 1980s and has slightly become a public health problem of worldwide magnitude. The pharmacist's role with clinical teams in hospitals that care for a patient with the HIV virus has led to a growing increase in patient adherence, as it is known that the pharmacist is the essential professional to accompany the patient throughout his/her trajectory. of drug use. This article aims to: Present the role of the pharmacist in adherence to Antiretroviral Therapy, in the management of care in HIV/AIDS. To this end, a bibliographic study of the literature review type, of a qualitative exploratory nature, was carried out in the following databases: SCIELO, MEDLINE, PUBMED and LILACS, in which only studies published between 2016-2021, in Portuguese, English, were selected. . It was possible to perceive that great advances have been achieved in Brazil in terms of legislation and universal and free access to antiretroviral therapy (ART) since the discovery of AIDS, however, therapeutic success requires high levels of adherence to treatment, which has a greater tendency when the multiprofessional team has a pharmacist who works clinically with the patient. Thus, more awareness is proposed about the need for professionals such as pharmacists who are on the front line with their pharmacotherapeutic knowledge in the treatment of HIV/AIDS.